1995
DOI: 10.1063/1.871376
|View full text |Cite
|
Sign up to set email alerts
|

Thermal equilibrium of bunched charged particle beams

Abstract: The Maxwell–Boltzmann distribution of a bunched charged particle beam is the state toward which every other distribution will relax. For beams with lifetimes much shorter than the time required for relaxation to equilibrium, it is the distribution at injection that minimizes the emittance growth due to relaxation toward equilibrium. Three-dimensional thermal distributions are found numerically for the case of linear external focusing forces acting on an axially symmetric bunched beam in a conducting pipe. Equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…At the high beam currents and charge densities of practical interest, of particular importance are the effects of the intense self fields produced by the beam space charge and current on determining the detailed equilibrium, stability and transport properties, and the nonlinear dynamics of the system. Through analytical studies based on the nonlinear Vlasov-Maxwell equations for the distribution function f b (x, p, t) and the self-generated electric and fields E s (x, t) and B s (x, t), and numerical simulations using particle-in-cell models and nonlinear perturbative simulation techniques, considerable progress has been made in developing an improved understanding of the collective processes and nonlinear beam dynamics characteristic of high-intensity beam propagation in periodic focusing and uniform focusing transport systems [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In almost all applications of the Vlasov-Maxwell equations to intense beam propagation, the analysis is carried out in the laboratory frame, and various simplifying approximations are made, ranging from the electrostatic-magnetostatic approximation [29], to the Darwin-model approximation [30][31][32][33][34][35] which neglects fast transverse electromagnetic perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…At the high beam currents and charge densities of practical interest, of particular importance are the effects of the intense self fields produced by the beam space charge and current on determining the detailed equilibrium, stability and transport properties, and the nonlinear dynamics of the system. Through analytical studies based on the nonlinear Vlasov-Maxwell equations for the distribution function f b (x, p, t) and the self-generated electric and fields E s (x, t) and B s (x, t), and numerical simulations using particle-in-cell models and nonlinear perturbative simulation techniques, considerable progress has been made in developing an improved understanding of the collective processes and nonlinear beam dynamics characteristic of high-intensity beam propagation in periodic focusing and uniform focusing transport systems [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In almost all applications of the Vlasov-Maxwell equations to intense beam propagation, the analysis is carried out in the laboratory frame, and various simplifying approximations are made, ranging from the electrostatic-magnetostatic approximation [29], to the Darwin-model approximation [30][31][32][33][34][35] which neglects fast transverse electromagnetic perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive numerical investigations of Eqs. (6) and (7) have been presented in the literature [1,2,[11][12][13][14][15][16][17] which characterize the equilibrium solutions typically in terms of two parameters corresponding to the temperature T b and the on-axis number densityn b , or scaled versions thereof. The purpose of the present work is to show that appropriately normalized radial profiles for n 0 b ͑r͒ and f 0 ͑r͒ can be characterized in terms of a single dimensionless parameter d b defined by…”
mentioning
confidence: 99%
“…In addition, for present purposes, the particle motion in the beam frame is assumed to be nonrelativistic, and we consider the class of intense non-neutral beam equilibrium solutions ͑≠͞≠t 0͒ to the nonlinear Vlasov-Maxwell equations which are axisymmetric ͑≠͞≠u 0͒ about the beam axis and are continuous in the axial direction with ≠͞≠z 0. Denoting the four-dimensional transverse phase space by ͑x, y, x 0 , y 0 ͒, where x 0 dx͞ds and y 0 dy͞ds are (dimensionless) transverse velocities, and s b b ct is the normalized time variable, it is readily shown that distribution functions f 0 b ͑x, y, x 0 , y 0 ͒ of the general form [1,[11][12][13] …”
mentioning
confidence: 99%
See 2 more Smart Citations